The Safety and Efficacy of Bipolar Plasma-Kinetic Transurethral Resection of The Prostate in Patients Taking Low-Dose Aspirin - Wu, Jie; Li, Hongyan; Tao, Rongzhen; Tang, Qinglai (Urology Journal, 2023)
Purpose: To explore the safety and efficacy of bipolar plasma-kinetic transurethral resection of the prostate in patients taking low-dose aspirin. Materials and Methods: Benign prostatic hyperplasia (BPH) patients who underwent surgical treatment from November 2018 to May 2020 were retrospectively analyzed, and divided into two groups according to whether taking 100mg aspirin daily aspirin or not. The perioperative indexes, complications and sequelae also were used to evaluate safety. The efficacy was evaluated by the functional outcomes in 3,6,12 months. Results: There were no statistical differences in the baseline characteristics or perioperative indicators and complications and sequelae, except for a longer operative time(90.49 ± 14.34 vs 84.95 ± 15.49; 95%CI: 0.26-10.83; P = .040) and a shorter hospital stay time(HST) (8.52 ± 1.55 vs 9.09 ± 1 .50; 95% CI: 0.21-1.11; P = .042) in the non-aspirin group. During the 12-months follow-up period, the functional outcomes of the two groups were significantly improved except International Index of Erectile Function (IIEF-5). Conclusion: Based on our research results, PKRP a safe and effective method for patients with BPH who taking 100mg aspirin daily.